THE IMPACT OF HUMAN CAPABILITIES DEVELOPMENT ON QUALITY OF THE EMPLOYEE’S LIFE STYLE: A QUALITATIVE STUDY ON A GROUP OF THE ACADEMIC STAFF IN THE COLLEGE OF ADMINISTRATION AND ECONOMICS - UNIVERSITY OF MOSUL - Dr. Adel Muhammad Abdullah Al-Taei; Dr. Nidal Ali Suleiman (Scholars Digest Publishing, 2024)
Purpose: The aim of this research to find the cluster of Human Capabilities Development depend on Quality of the Employee’s Life Style Structure and methods: The research relied on the inductive approach, Hence, it is a transition from particulars to a general rule. The research relied on the College of Administration and Economics, University of Mosul, in testing the variables of the research’s title and its sub-dimensions by distributing 100 questionnaire forms, twenty sex valid questionnaires were received for analysis that was distributed via the Google Forms link. The results: we were used program SPSS Specifically cluster analysis that provides indicators that help test the hypotheses of the current research. practically contribute to determining the priorities of the most influential factors in building the quality of the career of the academic staff, which is built upon to provide the best educational services. Practical implications: The current research uses cluster analysis in the formation of the relationship between the detailed dimensions of human resources capabilities and the quality of career, the formation of the cluster of this relationship and the diagnosis of its conclusions.Originality / Value: This research is considered as one of the research applications related to the quality of lifestyle that meets great interest in current studies in Business Administration and addresses one of its dimensions, which is the quality of career of teaching staff in universities.
Keywords: human capabilities development, Quality lifestyle empowerment, work teams, mental openness, satisfaction with, tangible requirements, and promotion.